Postponed diagnosis of alpha-1 antitrypsin deficiency - Stojković-Lalošević Milica; Stjepanović Mihailo; Čolović Nataša; Marić-Živković Jasmina; Mihailović-Vučinić Violeta; Stojković Mirjana (Srpski Arhiv za Celokupno Lekarstvo, 2016)
nema